Roughness of Production Conditions: Does It Really Affect Stability of IgG-Based Antivenoms? - Sanja Mateljak Lukačević; Tihana Kurtović; Juraj Borić; Beata Halassy (Toxins, 2022)
Antivenoms contain either pure animal IgGs or their fragments as an active substance, and are the only specific therapeutics against envenomation arising from snakebites. Although they are highly needed, the low sustainability of such preparations’ manufacture causes constant global shortages. One reason for this is the stability of the product, which contributes not only to the manufacture sustainability, but the product safety as well. It has been hypothesized that the roughness of conditions to which IgGs are exposed during downstream purification disturbs their conformation, making them prone to aggregation, particularly after exposure to secondary stress. The aim of this research was to investigate how the roughness of the downstream purification conditions influences the stability properties of purified IgGs. For this purpose, equine IgGs were extracted from unique hyperimmune plasma by two mild condition-based operational procedures (anion-exchange chromatography and caprylic acid precipitation) and three rougher ones (ammonium sulphate precipitation, cation-exchange chromatography and protein A affinity chromatography). The stability of the refined preparations was studied under non-optimal storage conditions (37 °C, 42 °C, and a transiently lower pH) by monitoring changes in the aggregate content and thermal stability of the pure IgGs. Mild purification protocols generated IgG samples with a lower aggregate share in comparison to the rougher ones. Their tendency for further aggregation was significantly associated with the initial aggregate share. The thermal stability of IgG molecules and the aggregate content in refined samples were inversely correlated. Since the initial proportion of aggregates in the samples was influenced by the operating conditions, we have shown a strong indication that each of them also indirectly affected the stability of the final preparations. This suggests that mild condition-based refinement protocols indeed generate more stable IgGs.